2023
DOI: 10.3389/fnhum.2023.1153976
|View full text |Cite
|
Sign up to set email alerts
|

Increased spontaneous activity of the superior frontal gyrus with reduced functional connectivity to visual attention areas and cerebellum in male smokers

Abstract: BackgroundChronic smokers have abnormal spontaneous regional activity and disrupted functional connectivity as revealed by previous neuroimaging studies. Combining different dimensions of resting-state functional indicators may help us learn more about the neuropathological mechanisms of smoking.MethodsThe amplitude of low frequency fluctuations (ALFF) of 86 male smokers and 56 male non-smokers were first calculated. Brain regions that displayed significant differences in ALFF between two groups were selected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 88 publications
(89 reference statements)
1
1
0
Order By: Relevance
“…This may contribute to the dysfunction associated with chronic smokers. 36 During our study, we noticed a notable decrease in FC within the L-Cbe6 region among individuals with HM. We hypothesize that HM could lead to impaired functioning in the L-Cbe6, potentially causing difficulties in movement, balance, and posture in individuals with HM.…”
supporting
confidence: 51%
“…This may contribute to the dysfunction associated with chronic smokers. 36 During our study, we noticed a notable decrease in FC within the L-Cbe6 region among individuals with HM. We hypothesize that HM could lead to impaired functioning in the L-Cbe6, potentially causing difficulties in movement, balance, and posture in individuals with HM.…”
supporting
confidence: 51%
“…(Rose et al, 2011) showed in a small study of 15 participants that excitatory stimulation to SFG resulted in immediate reductions in self-reported craving and reductions in craving due to neutral cues. Two previous studies showed that in people who smoke, SFG demonstrated higher levels of spontaneous activity (Niu et al, 2023) and lower resting functional connectivity (Zhou et al, 2017) relative to controls.…”
Section: Dlpfc and Insulamentioning
confidence: 94%